North American entrepreneurs in Cuba: which entry mode and government affiliation strategy?. Issue 3 (2nd October 2018) - Vila-Lopez, Natalia; White, Graham
Abstract : Purpose: To have success in newly liberalized markets, firms must have a plan of action before resources are committed. What some companies do not realize is that their own entrepreneurial orientation (EO) will dictate their strategies, and performance outcomes, in both their home market and abroad. In order to maximize firm performance in newly liberalized markets (such as Cuba), firms must be able to objectively gauge their own EO. The paper aims to discuss these issues. Design/methodology/approach: Within this framework, the present paper will attempt to effectively measure the EO of decision-making managers from US companies that have an interest in entering the Cuban market. A final sample of 81 US managers accepted to collaborate. They were then split into two groups (high and low EO; with 41 and 35 managers in each group, respectively) and compared regarding three variables: entry mode strategy, government affiliation strategy, and performance outcomes. Findings: The results show that EO is related with performance, but not with the two proposed variables of entry mode and government affiliation. Originality/value: In sum, the added value of the paper is to link US managers' strategies and performance in a newly liberalized market which has been seldom studied: Cuba. The fields of entry mode strategies and government affiliation decisions in this newly liberalized market remain poorly investigated. Not all firms managed by highly entrepreneurial-orientated managers will decide to enter foreign markets and, on the contrary, domestic firms which are not interested in international markets can be run by highly entrepreneurial managers. This is due, in part, to the fact that internationalization can be driven by other factors. Therefore, this paper will attempt to demonstrate if certain entry modes will perform better than others when the foreign market is a newly liberalized economy. Additionally, the importance, and effect, of governmental relationships on performance outcomes will be tested within the research.